Role of Viral Envelope Proteins in Determining Susceptibility of Viruses to IFITM Proteins - Thomas Marceau; Martine Braibant (Viruses, 2024)
Interferon-induced transmembrane proteins (IFITMs) are a family of proteins which inhibit infections of various enveloped viruses. While their general mechanism of inhibition seems to be non-specific, involving the tightening of membrane structures to prevent fusion between the viral envelope and cell membrane, numerous studies have underscored the importance of viral envelope proteins in determining the susceptibility of viruses to IFITMs. Mutations in envelope proteins may lead to viral escape from direct interaction with IFITM proteins or result in indirect resistance by modifying the viral entry pathway, allowing the virus to modulate its exposure to IFITMs. In a broader context, the nature of viral envelope proteins and their interaction with IFITMs can play a crucial role in the context of adaptive immunity, leading to viral envelope proteins that are more susceptible to antibody neutralization. The precise mechanisms underlying these observations remain unclear, and further studies in this field could contribute to a better understanding of how IFITMs control viral infections.